Case report: Bilateral carotid body tumors with a concomitant skull-base paraganglioma - Liu, Zhixuan; Yue, Ruimin; Sun, Cuiyun; Wang, Junping (Frontiers in Oncology, 2023)
Background: Bilateral carotid body tumors with a concomitant skull-base paraganglioma are extremely rare, of which only one case has been reported in the literature to date. Case Presentation: We present the case of a 35-year-old male with 1 year of hypertension and high levels of dopamine and 3-methoxytyramine. Magnetic resonance imaging (MRI) scans demonstrated three separate masses at the left middle cranial fossa floor and bilateral carotid bifurcation. Genetic testing showed succinate dehydrogenase complex subunit D mutation. The patient underwent the resection of the left skull base mass. Histopathology and immunohistochemistry confirmed the presence of a skull-base paraganglioma. Conclusions: Succinate dehydrogenase complex subunit D mutation-associated bilateral carotid body tumors with a concomitant skull-base paraganglioma accompanied by abnormal dopamine and hypertension are extremely rare, which not only provides ideas for considering the association of gene mutations, biochemical abnormalities and clinical symptoms but also provides an expanded diagnostic spectrum for paraganglioma in atypical locations.